Aiming at Virtue in Plato - Vasiliou, Iakovos (Cambridge University Press, 2013)
In the Cleitophon, a short and strange dialogue attributed to Plato, the character “Socrates” speaks only twice. He accuses the eponymous interlocutor on the one hand of telling people that it is a waste of time to associate with him, while on the other of lauding contact with Thrasymachus, the infamous character from Book 1 of Plato’s Republic. Cleitophon replies that Socrates has not heard the whole story: he is in certain respects deeply impressed by Socrates, but in other ways sharply critica